2023
DOI: 10.1177/15910199231168669
|View full text |Cite
|
Sign up to set email alerts
|

The safety profile of single antiplatelet therapy with flow diverters: Systematic review and meta-analysis

Abstract: Background Dual antiplatelet therapy (DAPT) is frequently used in treating cerebral aneurysms with flow diverters (FDs), whereas single antiplatelet therapy (SAPT) is used mostly with coated FDs and in ruptured aneurysms. We conducted a systematic review and meta-analysis to explore the safety profile of SAPT in FDs. Methods PubMed, Web of Science, OVID Embase, OVID Medline, and Scopus were searched to 1st November 2022. Outcomes of interest included ischemic and hemorrhagic complications, conversion to DAPTs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Preliminary animal model studies found there to be significantly more thrombus formation in the PED-Shield group on aspirin versus the DAPT group [ 70 ]. A recent meta-analysis on ruptured and unruptured aneurysms demonstrated SAPT with aspirin resulted in significantly more thromboembolic and intracranial hemorrhagic complications than SAPT with prasugrel or ticagrelor [ 71 ]. However, there have been successful reports of aspirin monotherapy in flow diversion for unruptured aneurysms in patients with bleeding disorders [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary animal model studies found there to be significantly more thrombus formation in the PED-Shield group on aspirin versus the DAPT group [ 70 ]. A recent meta-analysis on ruptured and unruptured aneurysms demonstrated SAPT with aspirin resulted in significantly more thromboembolic and intracranial hemorrhagic complications than SAPT with prasugrel or ticagrelor [ 71 ]. However, there have been successful reports of aspirin monotherapy in flow diversion for unruptured aneurysms in patients with bleeding disorders [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study recently published has compared aspirin to ticagrelor or prasugrel in ruptured vs. unruptured aneurysms and coated vs. uncoated FDs (48). Their analysis suggested that aspirin as a monotherapy in FDs is associated with a relatively higher risk of ischemic events and the use of prasugrel or ticagrelor in ruptured aneurysms and coated FDs conveys potential promising outcomes (48). Another single retrospective study has introduced ticagrelor as a SAPT in 24 patients with 36 aneurysms, 14 of which were ruptured, who underwent FD stenting.…”
Section: Single Antiplatelet Therapies (Sapt)mentioning
confidence: 99%